Optimization of Sintering Ratio Control Based on Improved Ant Colony Algorithm - Lingang, Dai; Liangli, Zhang; Jingyan, He; Xiangjun, Guo; Fei, Zeng (Chinese Automation Congress (Online), 2019)
In an ironmaking sintering production process, the accuracy and consuming time of sintering raw material ratio control determine the sintering production efficiency and finished product quality. An optimization of sintering ratio control based on improved ant colony algorithm is proposed. It is fused by the strong search function characteristics of beetle antennae search (BAS) algorithm in the early stage, and then the timeliness of the sintering ratio control process with fused ant colony algorithm is improved. By using the matching process data collected by a sintering raw material ratio control experiment system, comparative analysis between traditional ant colony algorithm and BAS algorithm is carried out. The simulation results of improved particle swarm optimization, BAS algorithm, linear programming algorithm, fuzzy control method, ACO algorithm and fusion algorithm show that the fusion algorithm has higher matching accuracy and shorter matching time after 50 iteration searches, which indicates that the fusion algorithm is superior to the algorithm in matching accuracy and matching time.